Array Pattern Optimization (IntechOpen, 2019)
Array pattern optimization is a very important and necessary issue in the majority of modern communication systems in a variety of applications such as sonar, radar, navigation, wireless communications, and many other engineering fields. Classical methods for array pattern synthesis have worked mainly with analytical models that are linear, local and, thus, their performances were not optimum. They have always been designed with closed-form mathematical models. Unlike these analytical methods, the global optimization methods with powerful computing tools offer optimum solutions. During the last few years, the design of the antenna arrays has been a topic of significant research activity. This book presents recent advances in the field of array pattern optimization. It is targeted primarily toward students and researchers who want to be exposed to a wide variety of antenna array design and optimization. It includes five chapters as well as the introductory chapter. These five chapters are categorized into five different areas depending on the application. These applications are ordered to address interference suppression, electronic toll collection, mmWave and ultra-wideband, integrated antennas, and educational packages for modeling smart antenna for 5G wireless communications. The book has the advantage of providing a collection of applications that are entirely independent and self-contained; thus, the interested reader can choose any chapter and skip to another without losing continuity.